Alignment of English as a foreign language teachers’ understanding of classroom assessment practices - Ida Ayu Made Sri Widiastuti; Katie Weir; Heru Sukoco; Gunadi Harry Sulistyo (International Journal of Evaluation and Research in Education (IJERE), 2023)
A comprehensive understanding of classroom assessment is essential for improving students’ learning and teachers’ professionalism. This study was conducted to gain better information about teachers’ understanding of classroom assessment compared to their classroom practices. Semi-structured interviews and classroom observations were employed to collect the data. The collected data were then analyzed comprehensively using comparative and argumentative methods. The results were then presented descriptively to establish the findings. The findings showed that some teachers’ classroom assessment practices were consistent with their assessment understanding, while others were inconsistent. The findings suggest that different contextual factors may influence teachers’ classroom practices. Furthermore, English as a foreign language (EFL) teachers need to be re-trained on comprehending the influencing contextual factors to utilize their understanding of assessment in the classroom effectively.